Effect of Different Aging Temperatures on Interfacial Reaction between SAC305 and ENEPIG Surface Finish - Siti Rabiatull Aisha, Idris; Saliza Azlina, Osman; Ali, Ourdjini; Azmah Hanim, Mohamad Ariff (Trans Tech Publications, Switzerland, 2012)
In electronic packaging industry, they are now driven technology to green product by replacing leaded-solder with lead-free solder in order to fulfill the European Restriction of Hazardous Substance (RoHS) compliance. Thus, Sn-Ag-Cu lead-free solder family is one of candidates can fulfill this requirement. This study investigates the interfacial reactions during reflow soldering and isothermal aging between Sn-3.0Ag-0.5Cu (SAC305) and electroless nickel/ immersion palladium/immersion gold (ENEPIG). Reliability of solder joint is also examined by performing solid state isothermal aging at 125˚C and 150˚C for up to 2000 hours. The results revealed that after reflow soldering, (Cu, Ni)6Sn5 IMC is formed between solder and substrate while after aging treatment another IMC was found between (Cu, Ni)6Sn5 and substrate known as (Ni, Cu)3Sn4. Aging time and temperature of solder joints results in an increase of IMC’s thickness and changes their morphologies to become more spherical, dense and with larger grain size. In addition, the results also revealed that the thickness of intermetallics formed is proportional to the aging duration and temperature.